The Potential of Jamblang Bark Plants (Syzygium cumini (L) Skeels) as Anticancer: A Literature Review - Himyatul Hidayah; Ikhtianingsih, Windi; Surya Amal (Eureka Herba Indonesia, 2023)
Jamblang plant (Syzygium cumini) is one of the local fruits of Indonesia. All parts of this plant can be used for treatment, one of which is jamblang bark as an anticancer agent. Genus Syzygium family myrtaceae is one of the largest genera in Indonesia. The purpose of this literature review is to provide an overview of the active compounds contained in jamblang plants that work as anti-cancer. Based on the results of the research that has been done, the jamun plant contains the compounds β-sitosterol, friedelin, betulinic acid, flavonoids, terpenes, alkaloids, phenolics, ellagic acid, glucoside, anthocyanins, kaempferol, quercetin, isoquercetin, myricetin, tannins, carbohydrates, albumin, and so on which can be used as antiviral, cardioprotective, anti-inflammatory, anticancer, antidiabetic, carminative, antihypertensive, anti-atherosclerotic, antifungal, antioxidant and hepatoprotector. It can be concluded that the active compound that works as an anticancer is a chemical compound of flavonoids located in jamblang bark (Syzygium cumini (L) Skeels).